MESSENGER observations of Alfvénic and compressional waves during Mercury's substorms. Issue 15 (14th August 2015) - Sun, Wei‐Jie; Slavin, James A.; Fu, Suiyan; Raines, Jim M.; Sundberg, Torbjörn; Zong, Qiu‐Gang; Jia, Xianzhe; Shi, Quanqi; Shen, Xiaochen; Poh, Gangkai; Pu, Zuyin; Zurbuchen, Thomas H.
Abstract MErcury Surface, Space ENviroment, GEochemistry, and Ranging (MESSENGER) magnetic field measurements during the substorm expansion phase in Mercury's magnetotail have been examined for evidence of low‐frequency plasma waves, e.g., Pi2‐like pulsations. It has been revealed that the By fluctuations accompanying substorm dipolarizations are consistent with pulses of field‐aligned currents near the high‐latitude edge of the plasma sheet. Detailed analysis of the By fluctuations reveals that they are near circularly polarized electromagnetic waves, most likely Alfvén waves. Soon afterward the plasma sheet thickened and MESSENGER detected a series of compressional waves. These Alfvénic and compressional waves have similar durations (10–20 s), suggesting that they may arise from the same source. Drawing on Pi2 pulsation models developed for Earth, we suggest that the Alfvénic and compressional waves reported here at Mercury may be generated by the quasi‐periodic sunward flow bursts in Mercury's plasma sheet. But because they are observed during the period with rapid magnetic field reconfiguration, we cannot fully exclude the possibility of standing Alfvén wave.